2022
DOI: 10.1093/femsec/fiac015
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial microbiome dynamics across natural populations of the social spider Stegodyphus dumicola

Abstract: Host symbiont interactions may form obligatory or facultative associations that are context dependent. Long-term studies on microbiome composition from wild populations should assess the temporal and spatial dynamics of host-microbe associations. We characterized the temporal and spatial variation in the bacterial microbiome composition in six populations of the social spider Stegodyphus dumicola for 2.5 years, using 16S rRNA gene amplicon sequencing of whole spiders. Individuals within a nest exhibit highly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(43 citation statements)
references
References 72 publications
6
37
0
Order By: Relevance
“…Our results provide no evidence for a role of specific symbionts in shaping the observed metabolite profile pattern. The microbiomes of the S. dumicola spiders sampled along the climatic gradient showed no significant population-specific pattern (Figure 2), which is consistent with previous studies of S. dumicola spiders collected over even larger geographic distances (Busck et al, 2020(Busck et al, , 2022. The bacterial genera that dominated S. dumicola's microbiome in this study are identical to those previously found (Borrelia, Diplorickettsia, and Mycoplasma), and are so far not known to provide or enhance thermal tolerance in hosts.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results provide no evidence for a role of specific symbionts in shaping the observed metabolite profile pattern. The microbiomes of the S. dumicola spiders sampled along the climatic gradient showed no significant population-specific pattern (Figure 2), which is consistent with previous studies of S. dumicola spiders collected over even larger geographic distances (Busck et al, 2020(Busck et al, , 2022. The bacterial genera that dominated S. dumicola's microbiome in this study are identical to those previously found (Borrelia, Diplorickettsia, and Mycoplasma), and are so far not known to provide or enhance thermal tolerance in hosts.…”
Section: Discussionsupporting
confidence: 90%
“…Comparably, bacterial symbionts in the Asian citrus psyllid (Diaphorina citri) degrade during heat stress due to increased lysosomal activity, which provides nutrients to the surviving symbionts and host (Dossi et al, 2018). Busck et al (2022) estimated that for every host cell there are 1-2 bacterial cells in S. dumicola, and such a bacterial load could potentially influence the host metabolome upon cell lysis and supply the spider host with metabolites aiding its temperature response. Thus, S. dumicola with its microbiome may represent a parallel system to aphids and D. citri, where the microbial symbionts contribute to the host temperature response via cell lysis.…”
Section: Discussionmentioning
confidence: 99%
“…The spider microbiome was dominated by Mycoplasma, Diplorickettsia, Borrelia and Weeksellaceae (Figure S5), corroborating a previous study in Stegodyphus dumicola (Busck et al, 2020(Busck et al, , 2022.…”
Section: Bacterial Microbiomesupporting
confidence: 90%
“…Several aspects of precipitation associated more than expected with relative abundance of bacterial symbionts (Figure 6). A previous study showed an association between high precipitation and microbiome composition (Busck et al, 2022), and together these studies indicate that the microbiome composition of S. dumicola is shaped by aspects of humidity. This association is driven by 10 ASVs from different taxonomic groups that correlate strongly and/or significantly with aspects of precipitation (Figure S17).…”
Section: Association Patterns Between Climate Variables and Microbiom...supporting
confidence: 65%
See 1 more Smart Citation